Cytotoxic effects of heavy metals on functional attributes of boar sperm: an in vitro study - Kadirvel, Govindasamy; Diengdoh, Jasmine; Deori, Sourabh; Dewry, Raju Kumar; Abedin, Sayed Nabil; Moirangthem, Prabha (Frontiers in Environmental Science, 2023)
Objective: Reproductive toxicology is a field that deals with the effects of heavy metals on various aspects of reproduction, including sperm count, motility, viability, spermatogenesis, follicular atresia, hormonal imbalance, and oocyte maturation, among others. The present study was carried out to examine the effects of heavy metals, viz., arsenic (As), lead (Pb), and fluoride (F), on boar sperm quality parameters in vitro. Materials and Methods: Forty (40) ejaculates from six (6) boars, averaging eight ejaculates per boar, were collected with the gloved hand technique using a dummy sow. Six (6) different concentrations were selected for the in vitro study: 5, 10, 25, 50, 100, and 200 µM for As and Pb, and 5, 10, 25, 50, 100, and 200 mM for F. The ejaculates were co-incubated with heavy metals at these different concentrations and assessed after different incubation periods (0, 0.5, and 1 h) for sperm functional attributes, viz., sperm progressive motility, viability and membrane integrity, and sperm mitochondrial membrane potential (MMP). The combined effects of heavy metals on sperm functional attributes were also evaluated at different doses (5, 10, 25, 50, 100, and 200 μM/μM for As–Pb; 5, 10, 25, 50, 100, and 200 μM/mM for As–F; and 5, 10, 25, 50, 100, and 200 μM/mM for Pb–F). Results: The present study revealed a highly significant (p <0.001) decrease in sperm progressive motility, viable sperm, membrane integrity, and sperm MMP in samples treated with heavy metals under different incubation periods; furthermore, the longer the incubation time, the greater the toxicity. There was also a significant (p <0.05) decrease in sperm motility, membrane integrity, and MMP in the samples treated with combined heavy metals (As–Pb, As–F, and Pb–F), as compared to the control, after different incubation periods. A significant (p <0.05) reduction in sperm quality attributes was recorded even at the lowest concentrations in the case of heavy metal combinations. Conclusion: It can be concluded that As, Pb, and F are toxic to boar spermatozoa in vitro, causing reductions in sperm functional attributes in a dose- and time-dependent manner.